Palliative surgical treatment of gastric cancer - Estefan, A.; Beguiristain, A. (Cirugía del Uruguay, 1988)
The diagnosis of gastric cancer (GC), and therefore in potentially curative stage with surgery. it still remains today, and especially in our me: gave, an unsolved health problem.